Changing Norms about Gender Inequality in Education: Evidence from Bangladesh - Niels-Hugo Blunch; Maitreyi Bordia Das (Institute for the Study of Labor (IZA), 2014)
This paper examines norms about gender equality of the education of children and adults in Bangladesh using a recent household survey for two cohorts of married women. Education norms are found to differ substantially across cohorts, with women from the younger cohort being far more positive about female vs. male education of both children and adults. The effect of education in determining norms spans own and spousal education, as well as that of older educated females in the household, thus indicating sharing of education norms both within marriage and across generations. Detailed decompositions reveal that more than anything else it is the improvement in education across cohorts that has been driving the narrowing of the generational education norms gap in Bangladesh in recent years.
Keywords: D19; I29; J12; J16; J24; 330; gender education inequality norms; human capital; decomposition analysis; Bangladesh